Sialoadhesin-dependent susceptibility and replication of porcine reproductive and respiratory syndrome viruses in CD163-expressing cells - Lee, Hyun-Ji; You, Su-Hwa; Lee, Hyang-Sim; Shin, Yeun-Kyung; Cho, Yun Sang; Park, Tae-Sub; Kang, Seok-Jin (Frontiers in Veterinary Science, 2024)
Understanding the molecular interactions between porcine reproductive and respiratory syndrome viruses (PRRSVs) and host cells is crucial for developing effective strategies against PRRSV. CD163, predominantly expressed in porcine macrophages and monocytes, is a key receptor for PRRSV infection. CD169, also known as Sialoadhesin, has emerged as a potential receptor facilitating PRRSV internalization. In this study, we investigated PRRSV susceptibility in relation to CD169 expression in CD163-expressing cells. Susceptibility to PRRSV infection was estimated by immunostaining the N protein using SR30A and quantifying ORF7 using RT-PCR. PRRSV strains adapted to MARC-145 did not infect CD163+/CD169-cells but successfully replicated in CD163+/CD169+ cells. Similarly, porcine alveolar macrophage-isolated PRRSV strains effectively infected and propagated in CD163+/CD169+ cells compared to CD163+/CD169-cells (100% vs. 82.9%). We confirmed that high CD169 expression in CD163-expressing cells increases susceptibility to PRRSVs compared to low or no CD169 expression. In conclusion, CD169 expression level influences viral entry efficiency into CD163-expressing cells, providing valuable insights for isolating wild PRRSVs and producing high-titer PRRS vaccine candidates.